Günther Förg - a fragile beauty - Bell, Kirsty 1971-; Delahunty, Gavin 1977-; Le Feuvre, Lisa 1950-; Gillick, Liam 1964-; Luke, Megan R. 1977-; Richman, Lauren; Ruf, Beatrix 1960-; Saletnik, Jeffrey; Witkovsky, Matthew S. 1967- (Dallas Museum of Art, 2018)
Gunther Förg (1952-2013) was a German painter, sculptor, and photographer with an irreverent approach to abstraction. Förg's project tackled the latent instability between image and reality. His painterly surfaces may appear exquisitely sensitive, his installations elegantly precise, but these are mastered and executed with a cold detachment. His deft manipulations of the languages of abstraction obscured a darker message. This publication, the most comprehensive to date, offers an important new understanding of this extraordinary and complex artist. Three years in the making, it reinterprets Förg's oeuvre to reveal an artistic project that raises important questions about the traditional role of an object as a conveyor of fixed meaning. The book's subtitle-"A Fragile Beauty"-is an indication of how Förg successfully manipulated what is behind and beyond an object's appearance. Exhibition: Dallas Museum of Art, USA (21.01-22.04.2018); Stedelijk Museum Amsterdam, Netherlands (27.05-23.09.2018)
Published in conjunction with the exhibition ... exhibition schedule: Stedelijk Museum Amsterdam, May 26-October 14, 2018; Dallas Museum of Art, October 21, 2018-January 27, 2019
Keywords: Förg, Günther -- 1952-2013; Förg, Günther / 1952-2013 / Exhibitions; Painting, German / Exhibitions; Ausstellungskatalog -- Stedelijk Museum Amsterdam -- 26.05.2018-14.10.2018 -- Amsterdam; Ausstellungskatalog -- Dallas Museum of Art -- 21.10.2018-27.01.2019 -- Dallas, Tex.